Activating the back-quarters: strategies of acupuncture for the neglected open spaces of Delft South - Arnold, Anees (School of Architecture, Planning and Geomatics, 2017)
With regard to low-income settlemnts in Cape Town, it has become apparent that the private relam is prioritised over the public realm. It is essential that we regard the public realm as an integral component of the lives of the people who inhabit this environment. Because of the living conditions, large portions of people's lives are conducted outside of this prioritised private realm. It is evident that public spaces within these environments become neglected due to a lack of ownership and management. The intention of this research is to find strategies of enhancing public life through encouraging shared open spaces – the urban commons. This thesis is process driven as opposed to product driven. The objective is to determine a replicable strategy that possesses generic solutions as well as providing strategies to address the specific. These strategies are explored and hypothetically tested using Delft South, Western Cape, as a site. With regard to the public spaces the present condition of the public spaces are not dissimilar to that in other areas of the same socioeconomic condition in South Africa. The public spaces have been neglected and there is limited space to provide additional public spaces within these areas. Therefore this dissertation explores the possibility of activating existing residual open spaces as well as neglected parks. It aims to use these as opportunities to provide shared public spaces nestled within neighbourhoods to meet the needs of the respective communities. Ultimately, the objective of this thesis is to develop a series of strategies which can be applied to specific conditions. This is to be to be done by interrogating my own design processes with the objective of being able to reorder it in a suitable manner. Specific to Delft South the areas positioned away from the active Main Road require attention. For the case of this thesis theses areas are referred to the backquarters and I have highlighted it as my interest of concern An introduction to my interest of adding new life to the public back quarters through enhancing the neglected open spaces. I will start off by problematising public spaces in low-income suburbs to outline the underlying issues specific to South Africa. This is followed by general principles that public spaces should embody. A large section, thereafter, will analyse the spatial structure of Delft South and how it is being inhabited. This analysis was done using various exercises to get both a quantitative and qualitative understanding. Using this as a basis, desired outcomes are explained in the chapter following this. All of these aspects are used to inform the architectural interventions.